(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
In recent years, excessive use of social media has become widespread among students, significantly affecting their psycho-emotional state and cognitive functioning. This literature review aims to analyze the role of excessive social media use in the development of mental fatigue, emotional burnout, and depletion of cognitive resources among students. The findings indicate that prolonged and uncontrolled use leads to dysregulation of the dopaminergic system, attentional fragmentation, sleep disturbances, and reduced academic performance. Based on meta-analyses and epidemiological studies, it has been established that using social media for more than 3–4 hours per day increases the risk of developing mental fatigue by 1.5–2.3 times.